PERANCANGAN MEDIA PEMBELAJARAN E-LEARNING PADA SMA N 8 KOTA JAMBI - PANJAITAN, AVENI NATALIA; SADIKIN, ALI; IRAWAN, BENI (Jurnal PROCESSOR, 2018)
SMA N 8 Kota Jambi is one of the upper secondary education institutions. The learning process at SMA N 8 Kota Jambi experiences problems where teachers and students must meet face to face in the teaching and learning process and if the teacher is unable to attend the students do not get the lesson matter and there is limited time in doing the learning or doing the task and repetition in one meeting. To overcome these problems researchers do the design of e-learning learning media built using PHP and MySQL DBMS. The methods used in this research are from problem identification, literature study, data collection, problem analysis, system development and report generation. This e-learning application is expected to facilitate the teacher in distributing the subject matter, the tasks or repetition questions to the students and check the results of the exercises that students do, as well as a means of distance learning because the application is accessed online.